2007
DOI: 10.1055/s-2006-924561
|View full text |Cite
|
Sign up to set email alerts
|

GER1, a GDSL Motif‐Encoding Gene from Rice is a Novel Early Light‐ and Jasmonate‐Induced Gene

Abstract: The reaction of the rice mutant HEBIBA differs from that of wild-type rice in that the mutant responds inversely to red light and is defective in the light-triggered biosynthesis of jasmonic acid (JA). Using the wild type and the HEBIBA mutant of rice in a differential display screen, we attempted to identify genes that act in or near the convergence point of light and JA signalling. We isolated specifically regulated DNA fragments from approximately 10 000 displayed bands, and identified a new early light- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 51 publications
1
27
0
Order By: Relevance
“…Subclade Ib ( OsGELP2 3 63 77 84 , and 85 ) is expected to be involved in plant development and morphogenesis at the seedling stage according to the function of their close homologue GER1 ( OsGELP33 ) [56]. These genes are not only expressed in many rice organs and development stages, as well as share analogous gene structure and special protein motif 32, but also change their expression dramatically under stress conditions during early plant development (Figures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subclade Ib ( OsGELP2 3 63 77 84 , and 85 ) is expected to be involved in plant development and morphogenesis at the seedling stage according to the function of their close homologue GER1 ( OsGELP33 ) [56]. These genes are not only expressed in many rice organs and development stages, as well as share analogous gene structure and special protein motif 32, but also change their expression dramatically under stress conditions during early plant development (Figures.…”
Section: Discussionmentioning
confidence: 99%
“…The OsGELP63 gene is induced by both red and far-red light and by jasmonic acid, and acts in response to drought and cold stresses [79]. The study of OsGELP33 ( GER1 ) has demonstrated the role of this gene in the rice plant development at the seedling and coleoptile elongation stages [56]. OsGELP33 , together with its sister genes OsGELP84 and OsGELP3 , arose from the segmental duplication event (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the enzyme regulates positive feedbacks of jasmonate production during an injury response or stress. Furthermore, GER1 gene (GDSL containing enzyme rice 1) containing a GDSL motif was responsible for the light regulated JA response (Riemann et al, 2007), suggesting that the GDSL esterase/lipase could also be part of the defense mechanism mediated by jasmonate (Chepyshko et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…RBX1 (RING box protein 1) E3 ubiquitin ligase (13B5) plays a pivotal role in the maintenance of genome integrity (Jia et al ), alleviating cells from the genetic damage caused by UV‐B irradiation (Rozema et al ). GDSL‐motif lipases (GDSLs and 13A11) have been studied in various plants and function mainly in the regulation of plant development and defense response involved in jasmine acid, ethylene, light and auxin signaling (Oh et al , Ling et al , Riemann et al , Kwon et al , Lee et al ). The expression of GDSL ( 13A11 ) is UV‐B inducible in both ‘Mutsu’ and ‘Tsugaru’ (data not shown).…”
Section: Discussionmentioning
confidence: 99%